Database management and zooarchaeology : proceedings of the workshop on data management of archaeozoological assemblages, Amsterdam May 7-9 1984 : proceedings of the data management section of the international symposium on data management and mathematical methods in archaeology, Amsterdam May 10-12 1984 (Strasbourg)
206 s.